Budaya Organisasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan - Ardi Hadi Saputra; Deslida Saidah (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
The purpose of this study is to determine the effect of Organizational Culture and Work Environment on Employee Performance at Direktorat Pemasaran dan Pelayanan PT Angkasa Pura I (Persero) Kemayoran. The research method used quantitative research with multiple linear regression analysis techniques. The population in this study was employees of Direktorat Pemasaran dan Pelayanan PT Angkasa Pura I (Persero) Kemayoran and the sample was saturated with a total of 36 samples. The results show that Organizational Culture and Work Environment on Employee Performance has a strong influence. From the coefficient determination, the contribution value of the Organizational Culture variable and Work Environment variable on Employee Performance is 51.7%, while the remaining 48.3% is another variable which is not examined in this study.